MANAJEMEN FUNDRAISING WAKAF TUNAI UNTUK MENINGKATKAN PEROLEHAN WAKAF TUNAI (STUDI PENELITIAN PADA LEMBAGA MANAJEMEN INFAQ (LMI) BLITAR) - Fina Fathma Azizah; Ahmad Supriyadi (Bajang Institute, 2022)
The background of this research is the Infaq Manajemen Institute of Blitar is one of the institutions that succeed in collecting the cash waqf and use it supervision in accordance with the needs of the local community. This can happen because fundraising management is applied by the institution runs well so that the cash waqf of obtained optimal. This research uses qualitative research approach and field study research type. Data collection techniques are obtained by indepth interviews, documentation, and observations. The data collection technique is done by condensing data, data exposure and drawing conclusions, while checking the validity of the findings by using the source triangulation method, triangulation method. This research was conducted at the Infaq Management Institute (LMI) Blitar. The results of this study indicate that: 1) Planning in the management of fundamental funds of cash waqf applied by Infaq Management Institute (LMI) Blitar: (a) long-term strategic program plan; (b) Designing budget and target; (c) Build a broadcast fund-based wakaf scenario. 2) In the implementation of Fundraising management of waqf waves by Infaq Management Institute (LMI) Blitar used two methods is direct fundraising method through socialization, magazine publishing, and program offerings to partners in collaboration with the institution. While the indirect fundraising method is done by using various social media and the use of fundraising digital platform. 3) Infaq management institutions (LMI) Blitar conduct control of 3 things: (a) Program development; (b) the development of funds; (c) The constraints faced both internally and external institutions